Determination of Food Crop Prices Based on Farmers' Exchange Rates in West Tojo - Yulianti Kalaba; Erny; Ayu Arini; Adinda Elfara Rizki Adam; Wira Hatmi; Mukhlis (Postgraduate, University of Mataram, 2026)
The agricultural sector plays a strategic role in regional development, particularly in food security, job creation, and economic growth. In Tojo Una-Una Regency, agriculture, forestry, and fisheries accounted for 38.78% of the regional Gross Domestic Product in 2023; however, this contribution has not yet fully translated into improved farmer welfare. This study aims to determine food crop prices using the Farmer’s Price Index in Tojo Barat Subdistrict. A quantitative descriptive approach was employed using primary data from 35 rice farmers selected through proportional random sampling. Data were collected through structured questionnaires, interviews, and field observations. The determination of food crop prices was analyzed by calculating the price index received by farmers (IT), the price index paid by farmers (Ib), and the resulting FPR. The results of the study indicate that production costs increased by 9.04%, household food expenditures by 23.66%, and farmers’ income by 10.94%, resulting in income growth of 12.07%. The calculated IT was 112.35, and Ib was 111.84, resulting in an FPR value of 100.46. This indicates a marginal surplus with limited improvements in welfare. The narrow gap between IT and Ib indicates high vulnerability to price fluctuations. Policy interventions focused on input subsidies, price stabilization, and market access are needed to ensure the sustainable well-being of farmers.